Molecular transmission network characteristics and high-risk transmission analysis of newly reported HIV-1 subjects in Nantong, China - Wang, Dongyang; Zhou, Xiaoyi; Yuan, Tianze; Xia, Hongli; Liu, Kai; Chen, Anni; Zhu, Ping; Zhuang, Xun (Frontiers in Immunology, 2025)
IntroductionNantong is currently experiencing an HIV-1 epidemic. However, detailed information regarding the local transmission chains remains limited. This study aimed to combine genomic, epidemiological, and spatial data to investigate the genotypes, drug resistance, and transmission patterns of newly reported HIV-1 subjects in Nantong.MethodsA total of 1619 newly diagnosed HIV-1 cases were identified, of which 1203 valid sequences were included for analysis. The HIV-1 pol genes were amplified and sequenced for the analysis of genotype, drug resistance, and molecular transmission network. Logistic regression was used to identify factors associated with being within the molecular transmission networks. Spatial analysis was conducted using intensity matrices of HIV-1 transmission links between regions.ResultsAmong the 1,203 subjects, the male-to-female ratio was 4.3:1, with a median age of 49 years (IQR: 33-58). Phylogenetic analysis indicated that CRF07_BC was the dominant strain, followed by CRF01_AE and CRF55_01B. The overall prevalence of pretreatment drug resistance was 9.3%, with V179E as the most common mutation. The molecular transmission network was constructed at a 0.5% genetic distance threshold. Of 1,203 valid sequences, 326 (27.1%) were incorporated, forming 116 clusters ranging from 2 to 17 sequences, including 31 clusters with ≥3 sequences. Multivariate logistic regression analysis indicated that individuals aged 70 years or older (OR=2.17, 95% CI:1.02-4.62), infected with subtype C (OR=1.98, 95%CI:1.11-3.54), CD4+ cell counts of 200-500 cells/μL(OR=1.85, 95%CI:1.29-2.65) and >500 cells/μL (OR=1.87, 95%CI:1.08-3.27) were more likely to be within the molecular transmission networks. Spatial analysis found that the proportion of inter-city transmission was lowest in Rudong (46.8%) and highest in Tongzhou (80.2%).DiscussionThe HIV-1 epidemic in Nantong was characterized by the increasing dominance of CRF07_BC, rising pretreatment drug resistance, and extensive inter-city molecular clustering. Older people, particularly older men, are emerging as a critical population sustaining local transmission. These findings highlight the need for continuous molecular surveillance and region-specific prevention strategies tailored to high-risk groups to mitigate further HIV-1 spread.